(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
Chronic suppurative otitis media (CSOM) is a common disease among both children and adults and is characterized by a prolonged inflammatory process in the middle ear cavity. In this pathology, the condition of the local and systemic immune system is one of the key factors determining the clinical course of the disease and the response to treatment.